2004
DOI: 10.1093/rheumatology/keh304
|View full text |Cite
|
Sign up to set email alerts
|

Fall-related risk factors and osteoporosis in women with rheumatoid arthritis

Abstract: Fall-related risk factors predictive of hip fracture are common in women with RA. Fall risk needs to be considered when RA patients are being treated for osteoporosis and further work needs to be done to help reduce the risk of falling and fracture in women with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
2
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 25 publications
1
21
2
6
Order By: Relevance
“…Other studies have indicated functional disability as a risk factor for falls, but in our study, although it was associated with poorer performance in physical tests, it was not correlated with falls [4,9,12,13,19,20,35]. In a prospective study with 80 patients in Japan, Hayashibara et al [6] found no relationship between functional disability and the presence of falls and explained that the : chi-square; P: significance level findings were due to the fact that five of the eight HAQ categories assess the function of the upper limbs.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Other studies have indicated functional disability as a risk factor for falls, but in our study, although it was associated with poorer performance in physical tests, it was not correlated with falls [4,9,12,13,19,20,35]. In a prospective study with 80 patients in Japan, Hayashibara et al [6] found no relationship between functional disability and the presence of falls and explained that the : chi-square; P: significance level findings were due to the fact that five of the eight HAQ categories assess the function of the upper limbs.…”
Section: Discussioncontrasting
confidence: 66%
“…The incidence of falls in this sample of RA patients was high (48.8%) compared to that found in the literature, which shows ranges from 14.3 to 54% in retrospective studies and from 18.8 to 50% in prospective studies [4][5][6][7][8][9][11][12][13][14][15][16][17][18][19]. The incidence of falls observed was also high compared to that of noninstitutionalized elderly individuals, which ranges from 15.9 to 56.3% [2].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Die Prüfung von Koordination, Kraft und Balance bei einem komplexen Krankheitsbild wie der RA wurde zur Ermittlung des Sturzrisikos bisher wenig beschrieben [6,7]. In der hier vorgestellten Studie werden 3 verschiedene Test (CR-Test, TUG-Test und TS) gleichzeitig angewandt.…”
Section: Diskussionunclassified
“…Одним из осложнений РА яв-ляется вторичный остеопороз (ОП), на фоне которого у больных чаще, чем в популяции, возникают переломы позвонков, бедра и других костей [2][3][4]. Ведущими причинами возникновения ОП и переломов при РА яв-ляются хроническое воспаление, сопровождающееся активацией клеточного звена иммунитета и повышени-ем продукции провоспалительных цитокинов, прием глюкокортикоидов (ГК), снижение функциональной активности и высокий риск падений [5,6]. Имеются неоспоримые доказательства взаимосвязи снижения минеральной плотности кости (МПК) с активностью заболевания (DAS, СОЭ и уровнем С-реактивного бел-ка) [7][8][9][10], состоянием функционального статуса (HAQ) [3,4,7] и длительностью болезни [2,7].…”
unclassified